Impact of radiological morphology of clinical T1 renal cell carcinoma on the prediction of upstaging to pathological T3. (26th February 2020) - Teishima, Jun; Hayashi, Tetsutaro; Kitano, Hiroyuki; Sadahide, Kousuke; Sekino, Yohei; Goto, Keisuke; Inoue, Shogo; Honda, Yukiko; Sentani, Kazuhiro; Awai, Kazuo; Yasui, Wataru; Matsubara, Akio
Abstract: Objectives: Previous studies have reported that cases with clinical T1 renal cell cancer upstaging to pathological T3 are a risk factor to predicting postoperative recurrence after partial nephrectomy. The aim of our study was to investigate the impact of the radiological morphology of the enhanced CT scan of clinical T1 renal cell cancer on predicting upstaging to pathological T3. Methods: Three hundred sixty-seven cases with clinical T1 renal cell cancer diagnosed from enhanced CT scans were enrolled in this study. Based on the findings from the enhanced CT scan, the cases were classified into 'round', the margins of which were smooth and round; 'lobular', one or more findings of smooth dent and no spiky dent were identified on the margin of the tumor; and 'irregular', one or more spiky dent were identified on the margin of the tumor. The association of postoperative upstaging with these radiological morphology and other clinical characteristics of each case was analyzed. Results: Eighteen cases (4.9%) pathologically upstaged to T3a. Two round case (0.7%), 3 lobular cases (10.0%) and 13 irregular cases (22.0%) pathologically upstaged ( P < 0.001, round + lobular versus irregular). Four of 17 cases (23.5%) with hilar tumors pathologically upstaged, while 14 of 350 cases (4%) with tumors pathologically upstaged in other sites ( P < 0.001). Multivariate analysis revealed that irregular case was an independent factor in predicting upstaging to pathological T3a ( P < 0.001). Conclusions: Evaluation of the radiological morphology of clinical T1 renal cell cancer based on enhanced CT scans is useful for predicting pathological upstaging. Abstract : Of clinical T1 renal cancer, 4.9% pathologically upstaged to T3a. Multivariate analysis revealed that irregularity of tumor margin was an independent factor in pathological upstaging.